Management of malignant breast phyllodes tumor with rib invasion during pregnancy: a rare case report and literature review - Yu, Sijie; Li, Panni; Wu, Wenwen; Guo, Xianan; Chen, Huihui; Liu, Kexin; Ye, Dan; Teng, Zhihua; He, Wei; Wang, Liquan; Zhou, Yunxiang; Chen, Yiding (Frontiers in Oncology, 2026)
Phyllodes tumors of the breast are rare fibroepithelial neoplasms accounting for less than 1% of breast tumors, with malignant phyllodes tumors (MPTs) representing approximately one-quarter of cases. Occurrence during pregnancy is exceedingly uncommon and may be associated with accelerated tumor growth. We report a 32-year-old woman at 15 weeks of gestation with a two-year history of recurrent MPT who had undergone four prior excisions. During the current pregnancy, the tumor recurred with rapid progression and rib invasion. After multidisciplinary evaluation, radical extended resection with chest wall reconstruction using the latissimus dorsi muscle was performed in the second trimester without perioperative complications. The pregnancy continued uneventfully, and a healthy full-term infant was delivered. At six-month follow-up, no local recurrence or metastasis was detected. Herein, we present the first documented case of complete resection of a rib-infiltrating MPT during pregnancy and provide a comprehensive synthesis of the existing literature to inform the characteristics and comprehensive management of MPTs, with particular emphasis on surgical strategies. We also summarize available evidence on pregnancy-associated MPTs to characterize their clinical and biological features. These insights may inform individualized treatment planning and optimize the overall management of these rare tumors.